A utility minimization approach for energy-aware cooperative content distribution with fairness constraints - Yaacoub, Elias (2012)
Cooperation between mobile terminals (MTs) with the objective of energy minimization is studied. The purpose is to distribute a content of common interest to collaborating MTs while ensuring a reduced energy consumption. To reach this goal, the content is sent to selected MTs on a long-range link. Then, it is forwarded to other MTs on short-range mobile-to-mobile links. The problem is formulated as an optimization problem, and the optimal solution is shown to consist of sending the content to a single MT on the long-range link and of having that MT distribute it on the short-range links. This leads to an unfair energy consumption for the selected MT. Thus, to ensure fairness in energy consumption, a low complexity utility minimization algorithm is proposed. Using the appropriate utilities, the algorithm can be used to implement the optimal greedy energy minimization solution or to ensure different degrees of fairness in energy consumption. Practical constraints concerning the centralised and distributed implementations of the proposed algorithm are also discussed. Simulation results show that significant energy savings can be achieved with the proposed approach compared with the non-collaborative case. In addition, a tradeoff between fairness and energy savings is achieved depending on the utility selected